Analisis Manajemen Risiko Produk Pembiayaan Multijasa Pada PT. Bank Tabungan Negara Syariah - Milasari, Siti; Isfandayani, Isfandayani (At-Tamwil: Journal of Islamic Economics and Finance, 2024)
This research discusses the risk management analysis carried out by PT. Sharia State Savings Bank towards multi-service financing products. The method used in this study is descriptive qualitative, the data collected in this study is in the form of words, sentences or images that describe the actual situation. The author collects data through observation, interviews, and documentation to facilitate the research process. The results showed that the risks faced by PT. Sharia State Savings Bank towards multi-service financing, namely financing risks and operational risks. The application of risk management carried out by PT. Sharia State Savings Bank is by conducting an identification process by looking at 5C (Character, Capacity, Capital, Collateral, Condition Of Economy), measuring by looking at the NPF value every month, monitoring by providing daily report updates, as well as controlling with several collection processes, visits, saving financing using Reconditioning and Rescheduling, as well as conducting collateral auctions. Pt. Sharia State Savings Bank has carried out risk management of multi-service financing properly and in accordance with PBI No. 13/23/PBI/2011 concerning the Application of Risk Management for Sharia Commercial Banks and Sharia Business Units, namely a series of procedures and methodologies used to identify, measure, monitor, and control risks that arise.